zad.6
-4 × ( ¾x² + 2x - 1 ) = -4 × ¾x² + ( -4 ) × 2x + ( - 4 ) × ( - 1 ) = -3 x² - 8x + 4
4 × (¾x² -2x - 1) = 4 × ¾x² - 4 × -2x - 4 × 1 = 3x² + 8x - 4
( -¾x² -2x + 1 ) × ( - 4 ) = -4 × -¾x² + -4 × -2x + -4 × 1 = 3x² + 8x - 4
( ¾x² + 2x + 1 ) × ( -4 ) = -4 × ¾x² + -4 × 2x + -4 × 1 = -3x² -8x -4
( -¾x² + 2x + 1 ) × 4 = - 3x² + 8x + 4
( -¾x² + 2x - 1 ) × ( -4 ) = 3x² - 8x + 4
( - ¾x² + 2x - 1 ) × 4 = - 3x² + 8x - 4
( -4 ) × ( -¾x² - 2x - 1 ) = 3x² + 8x + 4
zad. 8
F = 3x - 5
G = 5 - 3x
F - G = ( 3x - 5 ) - ( 5 - 3x ) = 3x - 5 - 5 + 3x = 6x
Odp. D